2015
DOI: 10.1007/s00405-015-3622-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of partial superficial parotidectomy on amplitude, latency and threshold of facial nerve stimulation

Abstract: The aim of this study is to assess the effect of partial superficial parotidectomy and facial nerve dissection to electrophysiologic parameters of intraoperative facial nerve monitoring such as nerve stimulation threshold, stimulus amplitude and latency. Twenty-five patients who underwent partial superficial parotidectomy for benign parotid gland mass were included in the study. After the identification of the facial nerve main trunk, minimum stimulation threshold, latencies and amplitudes of the orbicularis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The purpose is to remove as much of the parotid tumoral mass as possible, along with the lobe, without damaging the nerve and therefore the facial muscles: frontalis, orbicularis oculi, nasalis, orbicularis oris, mentalis. The complete resection of the tumor is important because of the recurrence risk that subtotal resection might hold and also because of the pressure effect on the neighbouring structures 4 .…”
Section: Operative Policy and Surgical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose is to remove as much of the parotid tumoral mass as possible, along with the lobe, without damaging the nerve and therefore the facial muscles: frontalis, orbicularis oculi, nasalis, orbicularis oris, mentalis. The complete resection of the tumor is important because of the recurrence risk that subtotal resection might hold and also because of the pressure effect on the neighbouring structures 4 .…”
Section: Operative Policy and Surgical Resultsmentioning
confidence: 99%
“…All three cases were attended by the same surgeon in the classical Redon approach. The facial nerve was discovered near the stylomastoid foramen and dissection was performed following every branch of the nerve until the complete removal of the tumor and the lobe 4 .…”
Section: Operative Policy and Surgical Resultsmentioning
confidence: 99%
“…In recent decades, facial nerve monitoring (FNM) has been popularly applied as an adjunct during parotidectomy for: (i) early identification of the FN trunk; (ii) differentiation of the FN from other tissue and facilitation of FN branch dissection; (iii) confirmation of the functional integrity of the FN; (iv) detection of nerve injury and (v) prognostication of facial expression after resection of the parotid tumor [14][15][16][17][18][19][20][21][22][23][24][25]. However, due to lack of standard procedures for using FNM in parotidectomy, and lack of a proper system for grading facial function after parotidectomy, the value of FNM technology has been debated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that use of FNM does not significantly reduce the incidences of temporary and permanent facial dysfunction [14][15][16][17]. Others have reported that FNM decreases the risk of temporary facial weakness but not the risk of permanent facial weakness [18][19][20]. Sajisevi et al reported that patients who received revised parotidectomy with FNM had shorter operative time, less FN injury severity, and faster FN injury recovery compared with those without FNM [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent articles support the notion that intraoperative monitoring of the facial nerve reduces surgery time but has little impact on nerve dysfunction 6,7 . Fluorescent dyes have been used in laboratory research since the 1970s, and are an important tool for research into neural cell differentiation, neural regeneration, cell maturation and cell transplants 8 .…”
Section: Introductionmentioning
confidence: 99%